PENERAPAN PERATURAN DAERAH KOTA MEDAN TENTANG KAWASAN TANPA ROKOK DI KELURAHAN SUNGGAL - Afrita Afrita (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
The application of a No Smoking Area (KTR) is a space or area where smoking is prohibited, selling, advertising or promoting tobacco products. Places that are placed into smoking-free areas include health service facilities, learning places and schools, children's playgrounds, places of worship, public transportation, workplaces and public facilities, both government and private. This study examines how the implementation of the Medan city regional regulations regarding smoking-free areas and the effectiveness of the Medan city regional regulations regarding smoking-free areas in Sunggal Village. This researcher uses research methods. descriptive analytical with a normative juridical approach. Where the data and information will be collected both in terms of assessment and management. Secondary data in the form of primary, secondary and tertiary legal materials and the information are then analyzed juridically qualitatively with mandalam. The application of this Medan City Regional Regulation in Sunggal Urban Village. Since the issuance of the Medan City Regional Regulation, Sunggal Urban Village, especially the Sunggal Urban Village Office, have implemented a No Smoking Area. However, for those in the Sunggal sub-district, some residents still do not know about Medan City Regional Regulation Number 3 of 2014 concerning No-Smoking Areas. It is necessary to apply to each Head of the Environment in order to inform residents about the information of the Medan Kotam Regional Regulation Number 3 of 2014 concerning No-Smoking Areas and it needs residents' awareness to apply these regulations so that they can create a Smoking-Free Area in Sunggal Village.